Three new species of Aethina Erichson, 1843 from China (Coleoptera: Nitidulidae: Nitidulinae) - Zhang, Huan; Huang, Yu-Jie; Jelínek, Josef; Yu, Zhi-Zhou; Huang, Min (Zootaxa, 2026)
Three new species of the subgenus Aethina Erichson, 1843 from China are described and illustrated. Aethina (Aethina) arciformis Zhang & Huang, sp. nov. is described from Shanghai and belongs to the A. flavicollis species-group. Aethina (Aethina) montis Zhang, Huang & Huang, sp. nov. is described from Fugong, Yunnan Province, and belongs to the A. argus species-group. Aethina (Aethina) medogensis Zhang & Huang, sp. nov. is described from Mêdog, Xizang autonomous region, and belongs to the A. elongata species-group.